Immunomodulatory effects of bacteriocinogenic and non-bacteriocinogenic Lactococcus cremoris of aquatic origin on rainbow trout (Oncorhynchus mykiss, Walbaum) - Contente, Diogo; Díaz-Rosales, Patricia; Feito, Javier; Díaz-Formoso, Lara; Docando, Félix; Simón, Rocío; Borrero, Juan; Hernández, Pablo E.; Poeta, Patrícia; Muñoz-Atienza, Estefanía; Cintas, Luis M.; Tafalla, Carolina (Frontiers in Immunology, 2023)
Lactic Acid Bacteria (LAB) are a group of bacteria frequently proposed as probiotics in aquaculture, as their administration has shown to confer positive effects on the growth, survival rate to pathogens and immunological status of the fish. In this respect, the production of antimicrobial peptides (referred to as bacteriocins) by LAB is a common trait thoroughly documented, being regarded as a key probiotic antimicrobial strategy. Although some studies have pointed to the direct immunomodulatory effects of these bacteriocins in mammals, this has been largely unexplored in fish. To this aim, in the current study, we have investigated the immunomodulatory effects of bacteriocins, by comparing the effects of a wild type nisin Z-expressing Lactococcus cremoris strain of aquatic origin to those exerted by a non-bacteriocinogenic isogenic mutant and a recombinant nisin Z, garvicin A and Q-producer multi-bacteriocinogenic strain. The transcriptional response elicited by the different strains in the rainbow trout intestinal epithelial cell line (RTgutGC) and in splenic leukocytes showed significant differences. Yet the adherence capacity to RTgutGC was similar for all strains. In splenocyte cultures, we also determined the effects of the different strains on the proliferation and survival of IgM+ B cells. Finally, while the different LAB elicited respiratory burst activity similarly, the bacteriocinogenic strains showed an increased ability to induce the production of nitric oxide (NO). The results obtained reveal a superior capacity of the bacteriocinogenic strains to modulate different immune functions, pointing to a direct immunomodulatory role of the bacteriocins, mainly nisin Z.